Expression Pattern of Transcription Factors and Intracellular Cytokines Reveals That Clinically Cured Tuberculosis Is Accompanied by an Increase in Mycobacterium-Specific Th1, Th2, and Th17 Cells. (27th April 2015) - da Silva, Marcos V.; Massaro Junior, Vladimir J.; Machado, Juliana R.; Silva, Djalma A. A.; Castellano, Lúcio R.; Alexandre, Patricia B. D.; Rodrigues, Denise B. R.; Rodrigues, Virmondes
Abstract : Tuberculosis (TB) remains a major global health problem and is the second biggest cause of death by infectious disease worldwide. Here, we investigate in vitro the Th1, Th2, Th17, and Treg cytokines and transcriptional factors produced after Mycobacterium -specific antigen stimulation in patients with active pulmonary tuberculosis, clinically cured pulmonary tuberculosis, and healthy donors with a positive tuberculin skin test (TST+). Together, our data indicate that clinical cure after treatment increases the percentages of Mycobacterium -specific Th1, Th2, and Th17 cells compared with those found in active-TB and TST+ healthy donors. These results show that the host-parasite equilibrium in latent TB breaks in favor of the microorganism and that the subsequent clinical recovery posttreatment does not return the percentage levels of such cells to those observed in latent tuberculosis. Additionally, our results indicate that rather than showing an increase in the percentage of Mycobacterium -specific Tregs, active-TB patients display lower Th1 : Treg and Th17 : Treg ratios. These data, together with lower Th1 : Th2 and Th17 : Th2 ratios, may indicate a mechanism by which the breakdown of the host-parasite equilibrium leads to active-TB and changes in the repertoire of Mycobacterium -specific Th cells that are associated with clinical cure after treatment of pulmonary tuberculosis.